Evaluation of adversarial attacks against deep learning models - Lam, Sabrina Jing Wen (Nanyang Technological University, 2023)
The aim of the project is to evaluate and improve adversarial attacks against deep learning models. Specifically, this project will focus on attacks on deep learning models specific to image processing and classification and will only take references from defense methods. The definition of evaluation and improvement for this project would be to improve attack timings under the same computing resource and target model.